KEPENTINGAN INDONESIA DALAM PEMBERANTASAN KORUPSI MELALUI APSC (ASEAN POLITICAL-SECURITY COMMUNITY) - Arwiyanto Jody Amalino; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research discusses about the national interest of Indonesia in corruption eradication agenda through ASEAN Political-Security Community. As a nation, Indonesia has been trying to eradicate corruption because it has been ruining Indonesia’s vision to ensure the prosperity and security of its people. The eradication agenda became priority as the level and impact of corruption escalated drastically in Soeharto’s reign and fall. Corruption becomes more complex as it involves international actors and using more complicate methods. Indonesia realized that different approach should be used to strengthen the eradication agenda, especially to use international cooperation. Researcher focused on the national interest of Indonesia that became a prominent factor of Indonesia to propose the corruption and non traditional security issues in the building process of ASEAN Community. It resulted on agreement to make a pillar of the community that focus on politic and security issues, namely as ASEAN Political-Security Community (APSC). The formulation of this research based on Rationalism perspective on International Relations, supported with various theories and concepts, such as national security, national interest, corruption and cooperation, arguments and facts. This research answered the hypothesis made by researcher that revealed ASEAN Political-Security Community becomes one of the instruments that can be used to strengthen the eradication of corruption agenda. It contains cooperation between ASEAN Member States on prevention and combat corruption, the establishment of good governance, and also to deal with the issues of transnational organized crimes. Keywords : Indonesia, national interest, corruption, security, ASEAN, ASEAN Political-Security Community